A Study of Construing the Experience of Rage in English and Vietnamese Novels from Functional Grammar Perspective - Nguyen Thi Tu Trinh (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
Among basic human emotions, rage or anger is probably the most common experience of human life in the real world. The aims of this paper are twofold: to explore how rage as a part of daily human experience is construed in English and Vietnamese novels within the framework of functional grammar elaborated by Halliday and Matthiessen (2014) and to compare functional realization of rage in the two languages on lexico-grammar and ideational metafunction ground. In other words, based primarily on the collected data of 15 English and Vietnamese novels, this study focuses on analyzing how the lexico-grammatical resources constitute emotional experience of rage congruently and metaphorically in English and Vietnamese. Received 13th August 2018; Revised 17th January 2019; Accepted 15th April 2019